Menggali Makna Akuntansi Perspektif Fresh Graduate Program Studi Akuntansi - Azizah, Imroatul; Jannah, Binti Shofiatul; Putri, Tsalis Cahyani; Arfiani, Arini; Alfarizi, Mohammad Salman (AKTSAR: Jurnal Akuntansi Syariah, 2022)
This article explores the meaning of accounting from a fresh graduate perspective. Through an interpretive approach with a transcendental phenomenological method, forms of social experience from the point of view of the informant who experienced it directly were explored more deeply through in-depth interviews. Three informants, namely accounting alumni, have just graduated and already have work experience. The phenomenological method emphasizes the meaning that arises from the individual conscious experience. The stages of the data analysis technique begin with identifying the noema or textual analysis. Next, the researcher did bracketing or structural analysis based on noema identification. This stage is carried out as a level of deep meaning (noesis). The relationship between noema and noesis provides an understanding of how noesis forms noema, which is called intentional analysis. Finally, the researcher will get to the idea that underlies all pure consciousness called eidetic reduction. This study concludes that there are three different understandings of accounting. Namely, accounting is magic, accounting is complicated, and accounting is balanced.